Rebuilding relationships on coral reefs: Coral bleaching knowledge‐sharing to aid adaptation planning for reef users: Bleaching emergence on reefs demonstrates the need to consider reef scale and accessibility when preparing for, and responding to, coral bleaching. (5th August 2021) - Ainsworth, Tracy D.; Leggat, William; Silliman, Brian R.; Lantz, Coulson A.; Bergman, Jessica L.; Fordyce, Alexander J.; Page, Charlotte E.; Renzi, Juliana J.; Morton, Joseph; Eakin, C. Mark; Heron, Scott F.
Abstract: Coral bleaching has impacted reefs worldwide and the predictions of near‐annual bleaching from over two decades ago have now been realized. While technology currently provides the means to predict large‐scale bleaching, predicting reef‐scale and within‐reef patterns in real‐time for all reef users is limited. In 2020, heat stress across the Great Barrier Reef underpinned the region's third bleaching event in 5 years. Here we review the heterogeneous emergence of bleaching across Heron Island reef habitats and discuss the oceanographic drivers that underpinned variable bleaching emergence. We do so as a case study to highlight how reef end‐user groups who engage with coral reefs in different ways require targeted guidance for how, and when, to alter their use of coral reefs in response to bleaching events. Our case study of coral bleaching emergence demonstrates how within‐reef scale nowcasting of coral bleaching could aid the development of accessible and equitable bleaching response strategies on coral reefs. Also see the video abstract here: https://youtu.be/N9Tgb8N-vN0 Abstract : Coral bleaching threatens coral reefs worldwide. We review the heterogeneous emergence of bleaching across reef habitats to highlight how reef end‐user groups, who engage with coral reefs in different ways, require targeted guidance for how, and when, to alter their use of coral reefs in response to bleaching events.